The peasant dislodging in Camagüey (1939- 1948) (Islas, 2023)
Introduction: The main subject of the article is peasant eviction in Camagüey between 1939 and 1948. The research focuses on the eviction of peasants by American companies and native landowners.Methods: The study employed theoretical methods, documentary analysis, and interviews with peasant leaders who were involved in these evictions in Hato Estero and Santa Lucía.Results: As a result of the research, many landless peasants had to migrate to urban areas and become agricultural laborers and employees. Others resisted the evictions and confronted the American companies and native landowners, successfully avoiding eviction, as in the case of Hato Estero.Conclusions: In conclusion, it was demonstrated through the general mobilization of progressive forces that The Francisco Sugar Company and the Sucesión Rodríguez Labradas had no legal rights over the lands.
Keywords: expansion; migration; peasants; agricultural laborers; eviction